Subordination Results for $p$-Valent Meromorphic Functions Associated with a Linear Operator (Analysis in Theory and Applications, 2014)
In this paper, by making use of the Hadamard products, we obtain some subordination results for certain family of meromorphic functions defined by using a new linear operator.
Keywords: Meromorphic functions; subordination; Hadamard product; linear operator.